Pembelajaran Mendesain Rumah Menggunakan Media Audio Visual Dengan Memanfaatkan Bandicam - Lovy Herayanti; Baiq Rina Amalia Safitri (Department of Physics Education, Universitas Mataram, 2019)
This research is motivated by the fact that teachers in learning have never used instructional media in the form of audio-visual or video in explaining learning materials for home design. This research is a development research (development research) with 4D design (define, design, developed, desimination). The study was conducted in the department of building engineering at SMKN 2 Kuripan especially on home design subjects. Retrieval of research data using project-based classical completeness tests. The results of the study, as many as 82.61% or 19 students thoroughly designed the house without having to do remidial, while the remaining 17.39% or 4 new people declared complete after remidial. In the second stage, students are assigned to practice the material by designing house plans. 100% complete results. Based on classical completeness data, bandicam-based audio visual media is proven to be able to provide effective learning.